The Implementation of Character Education among Students at Rahayu Chandra Bethania - Bena br Ginting; Dinaria br Sembiring (Insan Akademika Publications, 2026)
Character education is a strategic foundation of the Indonesian national education system, aiming to develop students who are not only academically competent but also possess integrity, ethical awareness, and social responsibility. Although character education has been conceptually integrated into educational policies and curricula, its implementation in schools continues to face various challenges. This study aims to describe and analyze the implementation of character education at Rahayu Chandra Bethania Elementary School, identify supporting and inhibiting factors, and formulate effective and contextual strategies for character education implementation. Employing a descriptive qualitative approach, the study involved all 50 students of the school as research participants. Data were collected through classroom and school activity observations, semi-structured interviews, and document analysis. Data analysis was conducted inductively through data reduction, data display, and conclusion drawing, while data validity was ensured through methodological triangulation. The findings indicate that character education is systematically implemented through structured and routine activities, including daily morning prayers, literacy and numeracy programs conducted from Tuesday to Thursday, Bible study sessions every Friday, and weekly Talent and Career Day activities on Saturdays. These programs have proven effective in fostering students’ religious values, discipline, responsibility, creativity, independence, and self-confidence. The consistency of program implementation, teachers’ role modeling, and a supportive school culture emerged as key factors contributing to the success of character education. This study confirms that integrating character education into daily school activities is an effective and sustainable approach to fostering holistic character development among elementary school students